2003
DOI: 10.1021/jm0304562
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Bulky 2-tert-Butyl Group Containing Primaquine Analogue That Exhibits Potent Blood-Schizontocidal Antimalarial Activities and Complete Elimination of Methemoglobin Toxicity

Abstract: To eliminate an unwarranted metabolic pathway of the quinoline ring, a set of two compounds, where C-2 position of the antimalarial drug primaquine is blocked by metabolically stable bulky alkyl group are synthesized. Compound 2 [R = C(CH(3))(3)] of the series has produced excellent antimalarial efficacy against P. berghei and highly virulent multidrug-resistant P. yoelii nigeriensis strain in vivo. Compound 2 was also evaluated for methemoglobin (MetHb) toxicity. This study describes the discovery of a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 15 publications
2
56
0
2
Order By: Relevance
“…Moreover, the anti-malarial activity of 2-tert-butylprimaquine was demonstrated against P. berghei, Plasmodium yoelii nigeriensis (in vivo) and P. falciparum (in vitro), exhibiting attributes of a new potent blood-schizontocidal. These are remarkable findings, as PQ itself is not a blood-schizontocide [165]. A latest report upholds that the remarkable blood-schizontocidal activity of 2-tert-butylprimaquine may be due to a disturbance of the heme catabolism pathways in the malarial parasite.…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the anti-malarial activity of 2-tert-butylprimaquine was demonstrated against P. berghei, Plasmodium yoelii nigeriensis (in vivo) and P. falciparum (in vitro), exhibiting attributes of a new potent blood-schizontocidal. These are remarkable findings, as PQ itself is not a blood-schizontocide [165]. A latest report upholds that the remarkable blood-schizontocidal activity of 2-tert-butylprimaquine may be due to a disturbance of the heme catabolism pathways in the malarial parasite.…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 94%
“…This produced almost 200 PQ derivatives (Tables 2-4) bearing diverse groups in one or more given positions of the ring [6,46,[161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179]. Globally, the most favourable substituent insertions towards anti-malarial activity where those of methyl groups at positions 4 and 2, tert-butyl at position 2, simultaneous insertion of ethyl substituents at positions 2 and 4 and pentyloxy at position 5, as well as insertion at position 5 of alkoxy, fluoro, and 3-or 4-substituted phenoxy groups [51,163].…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Synthetic pathways towards PQ derivatives using benzotriazole as a synthetic auxiliary could be divided into two major routes. The first was the one in which PQ reacted with BtcCl yielding PQ benzotriazolide 58, 52 which was the starting material for the preparation of PQ ureas 59, 52 carbamates 60 53 and polymer-PQ conjugates 61.…”
Section: Synthesis Of Primaquine Derivativesmentioning
confidence: 99%
“…It has been reported that introducing an alkyl or alkoxy group at position 2 of the aromatic ring reduces the toxicity of a compound (induction of methemoglobin). 20,21 Scheme 1 describes the synthesis of compound 1. Compounds 2-6 were synthesized in similar routes.…”
mentioning
confidence: 99%